Role of malaria partners in malaria elimination in Armenia - Davidyants, Vladimir A. (Malar J, 2019)
Malaria control and preventive activities in the countries of the World Health Organization Region for Europe (WHO/EUR) were strengthened within the framework of the Regional Roll Back Malaria strategy adopted by the member-states at the beginning of the 2000s. A political document “From control to malaria elimination” known as the “Tashkent Declaration” was unanimously endorsed by the member-states of the WHO/EUR with malaria problems in 2005. Since then, considerable progress has been achieved in the countries of the region, signified by the dramatic reduction of malaria incidence in conjunction with the prevention of re-establishment of infection on the territories where malaria was eliminated earlier. Several countries of the region had been certified by the WHO as free of local malaria transmission as a result of the activities of their National Malaria Elimination Programme, Armenia being one of the first in 2011. One of the main lessons learnt during the implementation of the activities by the National Malaria Elimination Programme in Armenia was that the development of an operational plan for malaria elimination required a comprehensive national effort. Full support, both political and financial, from the highest levels of government to smooth coordination between different government ministries, such as Agriculture, Defense, Finance, Health and Policy and Planning and others, was a prerequisite for operational success. The role and place of various partners in the achievement of malaria elimination in the country is discussed in this review. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12936-019-2814-y) contains supplementary material, which is available to authorized users.